Virtual reality as a research method: is this the future of photo-elicitation?. Issue 3 (3rd July 2019) - McLaughlan, Rebecca
Abstract : Photo-elicitation is a method commonly employed by researchers attempting to answer questions about the relationship between our built environment and wellbeing. Despite the benefits of this method, there are limitations to the spatial, material and atmospheric understanding obtainable from a two-dimensional image. Given the increasing accessibility of virtual reality (VR) technology, this article reports results from a study that sought to understand whether VR could be the next logical step for researchers who currently employ photo-elicitation. 43 participants were shown the foyer and atrium space of a cancer treatment centre across three different mediums: photographs (14), a virtual environment (11) and a visit to the physical space (18). The variances between data quality obtained across these three experiences was analysed to evaluate the effectiveness of VR-interviews as an alternative to both photo-elicitation and walk-through interviews. While there is much excitement about the possibilities of VR as a visual research method, little research critically evaluates the data quality obtainable using this new technology relative to more traditional methods. Finally, the article provides recommendations for optimising VR for research, relative to enhancing participant engagement and data richness